1993
DOI: 10.1007/bf00315487
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind comparison of the effects of carvedilol and captopril on serum lipid concentrations in patients with mild to moderate essential hypertension and dyslipidaemia

Abstract: We have studied 250 patients with mild to moderate essential hypertension (diastolic blood pressure 95-114 mmHg) and dyslipidaemia (high-density lipoprotein cholesterol (HDL-C) below 1.03 mmol.l-1, total cholesterol 5.17-9.05 mmol.l-1, and triglycerides 2.26-5.64 mmol.l-1) in a controlled double-blind, multicentre, parallel group trial. The patients took a fat-modified diet. After a 4-week placebo period, patients who continued to fulfil the selection criteria were randomly allocated to treatment with either c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…However, this assumption was also excluded because the correlation between f-T change and the TC change was insignificant. Although the mechanism of the decrease in TC remains to be clarified, another ACEI has been reported to decrease TC levels (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, this assumption was also excluded because the correlation between f-T change and the TC change was insignificant. Although the mechanism of the decrease in TC remains to be clarified, another ACEI has been reported to decrease TC levels (14).…”
Section: Discussionmentioning
confidence: 99%
“…In 250 patients with mild-to-moderate essential hypertension and dyslipidemia, carvedilol and captopril were equipotent (72). Ö stergren et al have reported that carvedilol and enalapril have similar blood pressure lowering effects (73).…”
Section: Comparisons With Angiotensin Converting Enzyme Inhibitorsmentioning
confidence: 99%
“…Rare unwanted effects have included bradycardia, cold hands and feet, angina pectoris, worsening of symptoms of intermittent claudication, depressed mood, rashes and sleep disturbance. Carvedilol does not appear to cause clinically significant changes in lipid profiles 17 , 18…”
Section: Unwanted Effects and Contraindicationsmentioning
confidence: 99%